Evidence of the Associations between Individual and Partner Autonomy Support and Physiological Stress in the Context of Conversations about Weight among Couples Who are Overweight or Obese during a 6-Month Intervention. Issue 8 (3rd July 2022) - Denes, Amanda; Crowley, John P.; Ponivas, Ambyre L. P.; Cornelius, Talea; Allred, Ryan J.; Gettens, Katelyn M.; Powers, Theodore A.; Gorin, Amy A.
ABSTRACT: The aim of the study was to examine the impact of supportive communication on acute physiological stress responses during weight-related conversations taking place throughout a couples' weight loss program. Participants were 47 married or cohabitating couples where each partner had a BMI of 25–40 kg/m 2 . Couples were randomized as a dyad into a traditional weight loss program or a program that also included training in providing support to one's partner throughout the weight loss process. Structured conversations between partners about weight management were videotaped at baseline and 6 months. Participants provided saliva samples before and after the conversations, which were assayed for cortisol and salivary alpha-amylase (sAA) to determine physiological stress and anxiety responses to conversations about weight. The results indicated that receiving support from one's partner when discussing weight-related issues was associated with greater physiological stress, as indicated by higher cortisol and sAA levels, whereas providing support to one's partner was associated with lower cortisol levels and higher sAA levels. The findings suggest that receiving support is not a universally positive experience, especially for populations facing health issues. The mixed findings for support provision align with previous studies identifying a negative association between affectionate communication and cortisol levels, as well as a positive association between sAA and anxiety and emotional arousal. The findings and their implications for understanding the physiological correlates of couples' conversations about weight are discussed.